La plancha de plomo en cubiertas y fachadas - Aramburu Maqua, Rocío (Materiales de Construcción, 1985)
A description is given of the properties of lead sheet for roofing and cladding purposes. Basic rules as far as installations are concerned are given, specially with respect to dimensions of the pieces, characteristics of Joints and fixings, and watertightness conditions. Compatibility of lead with other building materials is also taken into account, as well as elementary health and safety rules for its installation. Spanish standards on the subject are also reviewed.